Spatial Patterns and Low Education Associated with Early Marriage - Muhammad Syukri; Alvianda Asyila Zachrany; Nalsali Ginting; Lia Nurdini (Indonesian Journal of Global Health Research, 2022)
The incidence of early marriage in Muaro Jambi Regency has increased. No studies have been done on the distribution pattern and the relationship between education level and early marriage in Muaro Jambi Regency. This study aimed to identify the hotspots and low spots of early marriage, and the relationship between low education level with early marriage in Muaro Jambi regency in 2021. Global and Local Analysis Moran Index is used in this study to map hotspots and low spots for early marriage. Spatial regression is used to determine the relationship between education level and cases of early marriage. This study used an ecological study approach with the unit of analysis of 155 villages in Muaro Jambi Regency. Data on early marriage was obtained from the Mauro Jambi Regency Health and Family Planning Agency (BKKBN) report. The percentage of early marriage in Muaro Jambi Regency is 22.49%. This study found a positive autocorrelation of early marriage in 14 villages that fall into the hotspots area and 11 villages that fall into the low spots area. Using the SAR model, this study also found a relationship between education level and early marriage in Muaro Jambi Regency.